The relationship between the palace commandant V. A. Dedyulin and the rightists: ideological unity or mutually beneficial cooperation? - M. A. Knyazev (Омский научный вестник: Серия "Общество. История. Современность")
The article examines the problematic issue of the nature of the relationship between the palace commandant V. A. Dedyulin and representatives of right-wing political forces at the beginning of the 20th century. The purpose of the article is to determine what was the basis of interaction between V. A. Dedyulin and the right — ideological unity or mutually beneficial cooperation? The sources of the study are both published and unpublished documents, in particular, personal and business correspondence of the palace commandant from the collections of the Russian State Historical Archive. The idea of V. A. Dedyulin, established in historiography, as an ideological sympathizer of the monarchist camp is criticized and the liberal nature of the ideas of the head of the imperial guard is substantiated. The article concludes that the relationship between V. A. Dedyulin and the right was built on a pragmatic basis and was more likely to represent cooperation based on mutual benefit rather than ideological unity.